Revisiting Shi’a Influence in Idrisid Morocco: Governance, Legitimacy, and the Reconfiguration of Religious Identity - Muhammad Farhan (Abdurrauf Social Science, 2026)
This study revisits the influence of Shi’a in the context of the Idrisid Dynasty in Morocco through a political sociology perspective. It aims to analyze how religious legitimacy, particularly claims of descent from the Prophet Muhammad (Ahl al-Bayt), functioned as a foundation of political authority as well as a mechanism for the construction of religious identity in the early Maghrib. In addition, the study explores how this influence has been represented and reinterpreted in both historical narratives and contemporary socio-religious contexts. This research employs a qualitative approach based on library research, drawing upon classical historical sources and modern academic studies relevant to the Idrisid period and the early development of Shi’a. The analysis focuses on the relationship between power, legitimacy, and identity within society. The findings indicate that Shi’a affiliation in the context of the Idrisid Dynasty was primarily symbolic and political rather than a fully institutionalized theological system. Genealogical claims to the Ahl al-Bayt played a crucial role in strengthening political legitimacy amid social fragmentation and intergroup conflict. Over time, this influence underwent socio-cultural transformation, resulting in diverse interpretations within contemporary Moroccan society, both in the form of cultural practices and religious discourse. This study contributes to a deeper understanding of the relationship between religion and power in Islamic history, while also offering a critical perspective on the process of reconfiguring religious identity within modern social dynamics.